Wireless Control of Swarm Robotics for Industrial Automation - Joby, P. P. (IRO Journal on Sustainable Wireless Systems, 2022)
In the modern world, robots and robotic technologies are engaged extensively in industrial automation. The performance of the collaborative robots has resulted in utilizing them as primary forces in industries. In this paper, we propose the concept of swarm robotics to address the drawbacks of industrial automation. Wireless communication established in the robots and the control systems enabling automation. Swarm robotics is a technology where multiple robots together solve issues by developing advantageous structures and behaviors replicating nature like swarms of bees, fish or birds. Wireless technologies (4G, 5G and Wi-Fi) are employed that aids in controlling of multiple robots in distributed locations.
Keywords: Swarm robotics; wireless communication; industry 4.0; ROS; e-Puck.